We are much more than watchdogs: The dual identity of auditors at the UK National Audit Office. Issue 4 (7th November 2016) - Morin, Danielle; Hazgui, Mouna
Abstract : Purpose: Three decades ago, the National Audit Office (NAO) in the UK acquired the powers to evaluate the extent that the British Administration was managed with economy, efficiency and effectiveness. The NAO has since adopted a dual mission: to help Parliament hold government to account and to improve public service. This study aims to investigate value-for-money (VFM) auditors' internalisation of a dual organisational identity: "obstructive" actions as representatives of a Supreme Audit Institution (SAI) and "enabling good practice", induced by a will stated in the mission that the NAO authorities have adopted. Design/methodology/approach: The organisational identity held and promoted by VFM auditors working at the NAO was explored in this research project. The authors specifically examined the understanding of those who claim to be serving both Parliament and organisations audited in their quest for performance improvement. The authors prompted the auditors to explain how they manage to reconcile these seemingly incompatible roles, namely, that of guardians and watchdogs who must publicly report gaps noted and that of assistants in government's learning process. To this end, the authors conducted a field study at the NAO in September 2012 during which 21 auditors were interviewed individually and as part of two discussion groups. Findings: The findings indicate that the auditors interviewed do not perceive a dichotomy in NAO's double mission, which they believe to be congruent with their audience's expectations. They draw meaning and usefulness from their role of monitoring the Administration if they believe they have contributed to improve public affairs management. In their view, the singular role of guardian no longer suffices. The authors conclude that VFM auditors' recently acquired identity of "moderniser" reflects a self-efficacy expectation that prevents them from recognising the apparent paradox within their dual identity and that lets them fantasise about their real influence on the Administration. Research limitations/implications: Admittedly, the limited number of auditors interviewed and who took part in discussion groups is not conducive to generalisation of the conclusions to all auditors in the NAO or to other SAIs. However, although modest in number, the auditor respondents have accumulated many years of VFM audit practice and have contributed to the production of many reports. The respondents could therefore rightfully speak of their work as VFM auditors and as representatives of an institution such as the NAO. Practical implications: This study contributes to the debates about the place and role of SAIs in the control environment of Administrations. By soliciting testimonials from the actors working within the NAO, the authors could thus question certain a priori assumptions held by stakeholders in the political and administrative world for whom auditors are mere "watchdogs" of Administrations, and nothing more. Originality/value: The dual mission that the NAO has adopted (similar to many other SAIs) has been formally and publicly stated. It was therefore worth investigating how experienced auditors such as those interviewed had internalised this mission. The authors argue that this dual mission, perhaps inspired by the managerialist culture that has shaped changes to the British Administration (and many other occidental Administrations) since the early 1980s and that is seemingly encouraged by Government, twists the legislator's intentions, which are to consider SAIs' auditors as guardians and watchdogs of Administrations, not as agents of change and improvement.